Effectiveness of cold coagulation in treating high-grade cervical intraepithelial neoplasia: the human papillomavirus evidence of cure - Tadesse, Workineh G.; Oni, Atobatele A. A.; Hickey, Kevin P. W. (Journal of obstetrics and gynaecology, 2019)
We retrospectively analysed post-treatment human papillomavirus (HPV) results in women treated for cervical intraepithelial neoplasia (CIN) to establish if 'virological cure' rates achieved by cold coagulation matched those for large-loop excision of the transformation zone (LLETZ) in the treatment of CIN. The main outcome measure was the rate of non-detection of HPV at 6- and 18-month follow-up. HPV was not detected in 82.0% and 86.0% of women at 6- and 18-month follow-up, respectively. In women with high-grade CIN (CIN 2 or worse), there was no difference in HPV non-detection rates among the two treatment methods at six-month (81.8% for cold coagulation vs. 84.0% for LLETZ, χ 2 =0.23, p value=.632), and 18-month follow-up (83.3% for cold coagulation vs. 89.2% for LLETZ, χ 2 =1.46, p value=.227). Cervical cold coagulation provides a high 'virological cure' rate for all grades of CIN, equivalent to that seen with LLETZ. Impact Statement What is already known on this subject? It is well established that CIN cure rates after treatment with cold coagulation are comparable to those of excisional methods and are over 90% on cytological follow-up post-treatment. Furthermore, there are no demonstrable adverse effects on fertility and delivery in pregnancies conceived after cold coagulation according to long-term follow-up studies. In contrast, there is a positive correlation between treatment with LLETZ and the risk of subsequent subfertility and adverse pregnancy outcomes. What the results of this study add? This study provides evidence that cold coagulation achieves similar cure rates to that of LLETZ not only in cytology but also in HPV test of cure. This finding is significant as we are moving to a primary HPV cervical screening programme. What the implications are of these findings for clinical practice and/or further research? A negative high-risk HPV test provides a greater reassurance of a low risk of CIN 3 or cancer than a negative cytology result. Therefore, given parity to LLETZ in 'virological cure' rate and having no known adverse effects on fertility and pregnancy, cold coagulation should be used to treat most cases of CIN, especially in women of reproductive age.